Return On Assets dan Current Ratio Terhadap Price To Book Value Dengan Dividend Payout Ratio Sebagai Variabel Intervening (Pada Perusahaan Yang Terdaftar Di BEI Periode 2018-2020) - Dilla Anggraini; Indah Yuliana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The main objective of this research is to analyze and quickly see where legacy returns lie and their current relationship with industry value (from price to firm value). What if the dividend payout ratio is added as an intervention variable? The analytical tool used in this study is SmartPLS and the population used in this study is the industry listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The study results show that the current ratio has a positive and insignificant effect on the dividend payout ratio. This ratio only has a negative and insignificant effect on the dividend payout ratio. This ratio will have a negligible negative impact on industry prices and values. The effect of the dividend payout ratio on industry prices and values ​​is negligible. That is, the payment of dividends does not affect the price and value of the industry. Return on assets has a significant correlation with the dividend payout ratio and is not significant. Return on assets has a positive correlation with the dividend payout ratio and is not significant. Due to this dividend payout ratio, the return of this legacy has minimal impact on the share price and new value. It is said that billions of dividend payout ratio can not reduce the relationship between inherited income and market value and new value. The effect of the current ratio on firm value from the price through the dividend payout ratio is positive and not significant. And the dividend payout ratio is considered insufficient to convey the relationship between the current ratio and the price and value of the firm.